A Kinetic Study on Carbothermic Reduction of Hematite with Graphite Employing Thermogravimetry and Quadruple Mass Spectrometry. Issue 9 (12th March 2013) - Jung, Sung‐Mo; Yi, Sang Ho
Abstract The reduction of hematite–graphite pellet was investigated from a kinetic viewpoint in the temperature range of 1173–1473 K (900–1200°C). The experimental procedure included thermogravimetric analysis (TGA) for measuring the weight change of the pellet and quadruple mass spectrometry (QMS) for monitoring the compositional change of the product gases. By applying a uniform internal reduction model to the current system, the activation energies for the reduction of Fe3O4 to wustite and for that of wustite to Fe were evaluated to be 91.0 and 25.9 kJ mol−1, respectively. Due to the product gas analyses by QMS, it was observed that the reduction rate of hematite–graphite pellet was accelerated up to the equilibrium concentration of CO determined by the carbon gasification curve. Changeover of reduction mechanism with increasing reduction degree was explained in terms of a schematic diagram based on the results obtained in the current study.